Analysis of Regional Tax Management at The Regional Finance and Revenue Management Agency (BPKPD) of Cirebon City - Aurora Nurfitriani; Putri Pebriyanti; Dev Anand (Return : Study of Management, Economic and Bussines, 2024)
This research uses descriptive methods and qualitative approaches. The purpose of this study is to know, understand, and analyze the practice of the local tax implementation process as well as the obstacles that occur and efforts made in achieving regional tax management targets at the Regional Finance and Revenue Management Agency (BPKPD) of Cirebon City. Data collection techniques are carried out by means of interviews with the field of Regional Revenue Planning, Development and Evaluation (PPEPD). By showing the results that, in practice, BPKPD has been in accordance with the implementation of tax management based on applicable regulations. However, there are still decreases in local taxes including billboard tax, street lighting tax, underground water tax, and PBB-P2. Thus, BPKPD needs to make efforts in optimizing its regional tax management. The efforts made are; Conduct socialization for taxpayers in fulfilling their obligations in paying taxes owed. In addition, conducting a supervision system (tapping box) as an effort to report taxpayers' business turnover. Efforts were made, to fulfill the utilization for the facilities and infrastructure of the City of Cirebon.